TRENDS IN IMPROVING THE MANAGEMENT OF THE EUROPEAN MARITIME SHIP MARKET - MOSKVYAK, Yaroslava (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The modern cruise industry is a globally integrated industry in the world economy, which is associated with virtually all major industries (and sectors) of the world economy (from shipbuilding to the entertainment industry). The number of passengers traveling on cruise ships is increasing every year, and the income from this type of business is growing accordingly, so the organization of a cruise holiday is a very promising and profitable business. In general, a cruise is a sea tour, the basic cost of which includes comprehensive service on board. In particular: travel on the ship, accommodation in the cabin (depending on the chosen class), food, entertainment and, as a rule, a number of special events on board the ship (holidays, festivals, competitions, concerts, etc.). The globalization of the cruise industry and the growing number of cruise ports are dictating to the cruise market the need to join forces to achieve common development goals. A special place among such associations is occupied by the branding of cruise destinations, which involves the association of several ports in order to provide a particular tourist product. Since cruises are in constant demand from tourists from all over the world, the choice of the topic of this thesis is quite relevant. Cruise tourism is becoming an increasingly important part of the employment structure of advanced industrialized countries as well as developing countries. The modern cruise industry is a globally integrated industry in the world economy, which is associated with virtually all major sectors of the world economy. The globalization of the cruise industry and the growing number of cruise ports are dictating to the cruise market the need to join forces to achieve common development goals. The source base of the work are the works of famous domestic and foreign experts in the field of tourism, such as: Alexandrova A.Yu., Zhikhareva V.V., Kornilova V.V., Logunova N.A., Nezdoiminov S.G. etc., Internet sources and statistical information. The object of research is the organization of the process of cruise tourism in Europe. The subject of research is the current state of cruise tourism in the coastal regions of Europe. The aim is to study the current state and prospects of cruise tourism in Europe. Theoretical aspects of the organization of maritime tourism are determined, the peculiarities of the current state of the cruise market are described and the regulatory framework for the functioning of maritime travel is indicated. Prospects for the development of cruise shipping for the coastal regions of Europe are highlighted, as a result of which trends in improving the management of the European maritime shipping market are proposed.